Effectiveness and mechanism of corrosion inhibiting admixtures - Abdelalim, A. M. K. (2006)
Steel reinforced concrete is one of the most durable and cost effective construction materials but it can suffer in high chloride environments from corrosion due to chloride induced break down of the normal passive layer protection. One way of protection embedded steel reinforcement from chloride induced corrosion is by the addition of corrosion inhibiting admixtures (CIA) to the concrete mixes. In this paper, the effectiveness of various corrosion inhibiting admixtures (CIA), namely calcium nitrite and sodium benzoate, admixed with OPC mortar ingredients on fresh parameters (initial flowability and rate of flowability loss), microstructure related properties (cement-phase composition, capillary porosity and permeation) and reinforcement corrosion activity was extensively investigated. The role of these CIA on the mechanical properties (such as compressive, tensile and bond strength) of OPC matrix was also studied. Therefore, various 0.50 w/c OPC mortars made with 0, 2, 4 and 5% of either calcium nitrite or sodium benzoate were prepared and then assessed using mortar flow table, thermogravimetric analysis de-sorption test, initial surface absorption test and half-cell apparatus. The results emphasized that the beneficial role of corrosion inhibiting admixtures on enhancing the resistance of reinforcement against corrosion is significantly dependent on the modifications occur to the microstructure of OPC matrix as a result of inclusion of CIA. The use of calcium nitrite and sodium benzoate has led to reducing the capillary porosity and rate of water flow into OPC matrix and increasing the amount of C-S-H. The amount of enhancement in the microstructure related properties is generally increased with CIA content. Also, the tensile and bond strength are significantly improved as a result of admixing calcium nitrite in OPC mix, while, all studied mechanical properties (compressive, tensile and bond strength) have been degraded when sodium benzoate was utilized.